Correlation of acute suppurative otitis media with infant feeding position - Regina, M; Radhamani, K V; Sanu, Moideen P; Arun, G N; Mohan, Mogarnad (Indian Journal of Child Health, 2017)
Background: Acute otitis media (AOM) is the most common childhood illness necessitating medical therapy for children younger than 5 years. Long-term and exclusive breastfeeding is associated with protection against AOM. However, faulty feeding position and habits can lead to the occurrence of AOM in infants. Objectives: The aim of this study is to assess the risk of occurrence of AOM with faulty feeding positions during the 1st year of life. Materials and Methods: All breastfed infants